Development of low cost heterogeneous catalyst for biodiesel production - Sulaiman, Sarina (International Islamic University Malaysia (IIUM), 2015)
At present, heterogeneous catalyst is studied extensively for biodiesel production to replace homogenous catalyst. This is due to the limitation created by homogeneous catalyst where it cannot be reused, creates separation problem and not environmentally friendly. This reason causes increase in biodiesel production cost. Benefits of heterogeneous catalyst include insensitive to FFA content, easy separation of the catalyst from solvent, esterify and transesterify the process at the same time, can be reused and recycled and less corrosion problem. It is a great challenge to explore an ideal solid base catalyst that is effective, economical and environmentally friendly for biodiesel production. The use of heterogeneous catalyst from waste, e.g. shells of oysters, eggshells and shrimps are gaining importance, and these shells being waste material and can be obtained at low cost or small capital. Fish bone is a fishery waste that can be exploited as catalyst in biodiesel production. The bone could be washed and dried and ground to produce nearly pure calcium carbonate. Calcinations of calcium carbonate produces calcium oxide, a suitable catalyst for transesterification. In this research, fish bone will be used as a heterogeneous catalyst for biodiesel production.